Implementation of the Concept of Inclusive Development in the Legal Order - Robert Piszko (Communications of International Proceedings, 2021)
The aim of the paper it to specify the possible ways to introduce the economic concept of inclusive development into the legal order of a specific country of the European Union, in particular into the legal order of Poland as a country of Eastern Europe. Introduction of such a concept may be done in an institutional and non-institutional manner. Institutional introduction involves legal implementation of the concept of inclusive development into a legal order. In turn, non-institutional implementation requires the creation of non-legal conditions for the functioning of such a concept. Following the analysis, it turns out that a limited implementation is not effective. The paper’s goal is pursued by specifying the notion of implementation, and then of the concept of inclusive development of civil society, naming determinants of legal implementation, and determinants of non-institutional implementation. The results of the analysis can be found in the final part (Discussion and conclusions). The explanation of this problem is a novelty because so far the issue of implementation has been addressed in reference to law (a semantic group relating to the decision theory), in particular EU law. The paper employs the method of linguistic analysis and economic analysis of law (Brozek and Stelmach 2006, pp. 104-160).
Keywords: Inclusive development; implementation; interpretation of law; application of law